Characteristics of color and iron oxides of clay fraction in Archeological Dark Earth in Apui region, southern Amazonas - Aquino, Renato Eleoterio de [UNESP]; Marques, Jose [UNESP]; Costa Campos, Milton Cesar; Oliveira, Ivanildo Amorim de [UNESP]; Rabelo de Souza Bahia, Angelica Santos [UNESP]; Coutrim dos Santos, Luis Antonio (Elsevier B.V., 2016)
One of the marks left by prehistoric man in the Amazonas landscape are the dark-colored soil stains, Archeological Dark Earth (ADE), which are rich in organic matter, phosphorus and calcium. The color in this soil is presented as an attribute of difficult interpretation on the horizon, and the studies towards a better identification are important. In this sense, the objective of this study was to characterize the color and iron oxides of the ADE clay fraction in Apui region in southern Amazonas. Six trenches were opened, where these profiles were characterized morphologically, and also samples were collected per horizon for later performance of grain size analysis, flocculation, water clay dispersion and chemicals (pH in water and potassium chloride, calcium, magnesium, potassium, phosphorus, potential acidity, f, organic carbon and organic matter) and mineralogical analyses. The data were submitted to principal component analysis. Similar behavior in the studied profiles was found both in physical and chemical attributes. It was concluded that the hematite and goethite, determined by x-ray diffraction and diffuse reflectance spectroscopy, besides not presenting significant variations between the studied soils, present similar characteristics to non-anthropogenic Brazilian soils. The color measured by diffuse reflectance spectroscopy proved efficient to indicate variations among the ADEs, proving to be an innovative technique, efficient and promising for indirect quantification of soil characteristics in a simple and low cost manner. The results show that iron oxides demonstrate be sensitive indicators of pedoenvironmental conditions and pedogenic processes of Archeological Dark Earth. (C 2015 Elsevier BAT. All rights reserved.
Keywords: Anthropogenic horizon; Anthropogenic soil; Diffuse reflectance spectra; Hematite; Goethite